The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1245/s10434-020-09583-3
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Changes in Care for a Community Academic Breast Center and Patient Perception of Those Changes

Abstract: Background Philadelphia and its suburbs were an epicenter for the initial COVID-19 outbreak. Accordingly, alterations were made in breast cancer care at a community hospital. Methods The authors developed a prospective database of all the patients with invasive or in situ breast cancer between March 1 and June 15 at their breast center. Any change in a breast cancer plan due to the pandemic was documented, and the patients were grouped into two cohorts according to whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…Patients were also given a survey Generalized Anxiety Disorder two-item (GAD-2) questionnaire which revealed that 31.2% of patients screened positive for anxiety and depression. Interestingly this was not statistically different between women who had a change in care due to COVID-19 or rates of GAD-2 positivity for women with breast cancer outside of the COVID-19 pandemic [7][8]. From multiple studies on both the From these studies we see that there were changes implemented in the care of breast cancer patients.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Patients were also given a survey Generalized Anxiety Disorder two-item (GAD-2) questionnaire which revealed that 31.2% of patients screened positive for anxiety and depression. Interestingly this was not statistically different between women who had a change in care due to COVID-19 or rates of GAD-2 positivity for women with breast cancer outside of the COVID-19 pandemic [7][8]. From multiple studies on both the From these studies we see that there were changes implemented in the care of breast cancer patients.…”
Section: Introductionmentioning
confidence: 87%
“…The impact on cancer and non-cancer health outcomes may take years to fully understand. Another study captured changes across a health system in the northeast which was an epicenter of COVID-19 [7]. In this analysis 44% of patients experienced a change in treatment with 65.6% of patients with a change in treatment receiving NET and 34.4% experiencing a delay in surgery alone.…”
Section: Introductionmentioning
confidence: 99%
“…We also sought to assess if these changes were associated with negative reactions from patients related to their overall mental health, breast cancer care, and outlook. 3…”
Section: Pastmentioning
confidence: 99%
“…Lankenau Institute for Medical Research, Wynnewood, PA; 2 Lankenau Medical Center, Wynnewood, PA; 3 The Bryn Mawr Hospital, Bryn Mawr, PA…”
mentioning
confidence: 99%
“…Although the existing studies conducted on TTS changes among patients with breast cancer during COVID-19 are mainly cross-sectional, the available evidence confirmed a time-delay in cancer treatment. High mortality risk diseases, such as cancers should not be neglected during the pandemic ( 10 13 ) and priorities should be determined. To date, there has been no studies that have dynamically analyzed the pattern of TTS changes at different stages of the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%